Analgesic and Anxiolytic Effects of Gastrodin and Its Influences on Ferroptosis and Jejunal Microbiota in Complete Freund’s Adjuvant-Injected Mice - Chen, Xin; Wang, Jinyue; He, Zhixian; Liu, Xin; Liu, Huawei; Wang, Xing (Frontiers in Microbiology, 2022)
This study investigated the effects of gastrodin (GAS) on analgesic, anxiolytic, ferroptosis and jejunal microbiota in chronic inflammatory pain mice. The chronic inflammatory pain model of C57BL/6J mice was established by hindpaw injection of complete Freund’s adjuvant (CFA). After GAS treatment, thermal hyperalgesia test, mechanical allodynia test, elevated plus-maze (EPMT) and open-field test (OFT) were performed to assess the behavioral changes of pain and anxiety. mRNAs of FTHI, GPX4, HO-1 and PTGS2 and jejunal microbiota were measured by qPCR. In CFA-injected C57BL/6 mice, we found that the mechanical and thermal pain threshold was increased with treatment of GAS. In EPMT, the number of entries in open arms and retention times of open arms were increased by GAS. In the OFT, the time spent in the central area was also increased. Furthermore, GAS enhanced mRNA expressions of FTHI, GPX4 and HO-1, but decreased the expression of PTGS2 in a dose-dependent manner. GAS is effective in the treatment of mice chronic inflammatory pain and anxiety-like behaviors. It maybe exhibits potential neuroprotective effects through inhibition of ferroptosis independently of the intestinal microbiota.